The effectiveness of credit assessment policy of Bank Islam Malaysia Berhad Samarahan Branch / Sazali Unus - Unus, Sazali (2002)
Bank Islam Malaysia Berhad (BIMB) Samarahan Branch, experienced extreme increased in non-performance-financing (NPF) accounts after 3 year of it pronounce operation. The alarming increased had inspired researcher to conduct this research in determining the main caused. Since credit assessment played vital role in credit decision, this study therefore focus on the effectiveness of bank credit assessment practiced on the investigation of borrower’s character, capacity and condition factor. Survey had been conducted on bank’s existing customer as respondent. The main aim is to evaluate the effectiveness of credit assessment practiced. To identify what is the dominant factors that contribute to the non-performance-financing. The study is also to measure the profile of customer (respondent) in term of their demographic characteristic. Based on the finding outcomes, the character element is the dominant factor that has significant impact to performance of the NPF level. Therefore, it is concluded that the credit assessment method of Bank Islam Malaysia Berhad Samarahan Branch had failed to investigate and interpret the real character of potential borrower. Finally few recommendation was made to accommodate the deficiency based on theory developed by financial expertise on the credit management.